Preparation and luminescent properties of color-adjustable La1-x-ySiBO5: xTb3+, yEu3+ phosphor for NUV-LEDs - Wenyu Zhao; Jiacheng Zhao; Lele Gao; Huihui Cao; Xuening Ding; Songbo Li (PLoS ONE, 2026)
A series of La 1-x-y SiBO 5 :xTb 3+ , yEu 3+ phosphors was synthesized through high-temperature solid-state reaction. The crystal structure, morphology, and luminescence properties of the phosphors were characterized by employing X-ray diffraction, scanning electron microscopy, photoluminescence, photoluminescence excitation and fluorescence lifetime measurements. Results show that the excitation spectra of La 1-x SiBO 5 :xTb 3+ and La 1-y SiBO 5 :yEu 3+ overlap at 300–400 nm, and the La 1-x-y SiBO 5 :xTb 3+ , yEu 3+ phosphors emit yellowish green (530–560 nm) and red (580–650 nm) light under 377 nm excitation. When x = 0.05 and y increases from 0.005 to 0.05, the emission intensity of Tb 3+ decreases gradually, whereas that of Eu 3+ increases gradually. This trend indicates energy transfer from Tb 3+ to Eu 3+ and color change from green to yellow and then red. The fluorescence lifetime test further confirms energy transfer from Tb 3+ to Eu 3+ . The prepared LaSiBO 5 :Tb 3+ , Eu 3+ phosphors exhibit effective tunable emission and near ultraviolet excitation and thus have potential applications in White-LEDs.